Permacultures of transformation: steps to a cultural ecology of environmental action - Thomas Henfrey; Lucy Ford (Journal of Political Ecology, 2018)
This article examines a trend over the past two decades towards more explicit  politicization in some areas of the ecovillage movement, particularly where covillages engage with related grassroots movements for environmental and social change. It  does so using an expanded political ecology framework, also drawing upon 'Multi-level Perspective on Sustainability Transitions' and Gregory Bateson's Ecology of  Mind. It argues that apparently apolitical focii on lifestyle change and personal development have in some cases given way to overt recognition of the need for global political change. It attributes this to the global political economy of sustainability becoming more evident and critiques of dominant social, political and economic regimes more compelling and widely accepted.